Scaling an idealized infant nasal airway geometry to mimic inertial filtration of neonatal nasal airways. (April 2018) - Tavernini, Scott; Church, Tanya K.; Lewis, David A.; Martin, Andrew R.; Finlay, Warren H.
Abstract: Idealized extrathoracic airways are a valuable tool for the development and testing of pharmaceutical aerosol delivery devices. These airways are designed to mimic the average filtration properties of the extrathoracic airways of the population on which they are based. We have investigated the ability to scale a previously developed infant nasal airway to generate a model with the correct filtration properties to mimic the neonatal population. Prospective scale factors were identified based on the dimensions of realistic nasal replicas, and based on 50th percentile body mass, body length, and head circumference. Inertial deposition was measured for four geometrically similar idealized nasal airway models. These data were compared to deposition in nasal airway replicas based on computed tomography (CT) images of seven infants between the ages of 5 and 79 days. Isotropically scaling the model that mimics the infant population (average age approximately 9 months) by 0.75 produced a model that mimics the neonatal population (average age approximately 1 month). This scale factor was consistent with the ratio of model characteristic diameters (airway volume divided by surface area, D V/As ) and with the ratio of 50th percentile body lengths for the two average ages. A predictive correlation based on Reynolds and Stokes numbers was identified that provides deposition efficiency of this geometry for D V/As between 1.20 mm and 0.72 mm. This equation can be used to provide expected deposition characteristics of our idealized nasal model before construction at scales not specifically considered here. Highlights: Scaling an idealized infant nasal airway to mimic neonatal filtration is explored. Scale factors based on nasal geometry and infant demographics are proposed. In-vitro aerosol filtration of the model is compared to neonatal nasal replicas.